2018
DOI: 10.1080/20469047.2018.1466481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal HIV status and treatment duration on body composition of HIV-exposed and HIV-unexposed preterm, very and extremely low-birthweight infants

Abstract: Mothers receiving HAART could have increased risk of preterm delivery, and the duration of maternal HAART affects postnatal body composition of their infants. Body composition differs between HIV-exposed and HIV-unexposed preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We found that almost a third (28%) of infants stunted at 12 months were stunted at birth, suggesting an appreciable impact of fetal growth on long‐term stunting. There is some evidence that maternal ART or specific antiretroviral drugs may increase the risk of preterm birth and early stunting in HEU infants (Hofer et al, ; Powis et al, ; Strydom, Nel, Dhansay, & Van, ). As ART continues to be more widely used and the population of HEU children continues to grow, the relative contribution of ART‐associated linear growth faltering in the overall prevalence of stunting may be appreciable.…”
Section: Discussionmentioning
confidence: 99%
“…We found that almost a third (28%) of infants stunted at 12 months were stunted at birth, suggesting an appreciable impact of fetal growth on long‐term stunting. There is some evidence that maternal ART or specific antiretroviral drugs may increase the risk of preterm birth and early stunting in HEU infants (Hofer et al, ; Powis et al, ; Strydom, Nel, Dhansay, & Van, ). As ART continues to be more widely used and the population of HEU children continues to grow, the relative contribution of ART‐associated linear growth faltering in the overall prevalence of stunting may be appreciable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results were not impacted by the sanitation intervention, the HIV status of the participants or by the trimester of pregnancy at which the samples were taken. The risk of preterm birth and (very) low birthweight in women with HIV is increased [10] but this apparently is not through a change in the capacity of the microbiome to degrade resistant starch.…”
mentioning
confidence: 99%